PRISION MOTHER: THE WORK OF SOCIAL ASSISTENCE AND RIGHTS GUARANTEE - Villani, Camila Auricchio (Seven Editora, 2026)
This article deals with presenting a synthesis of the problematizations of maternal in women's penitentiaries. The research identified the characteristics of women in maternity in the female prison system, as well as analysed the difficulties these women face to get the respect of their human rights. Also coming to investigate how the women's prison system works and the importance of the social worker in the performance and care of the woman in the maternity situation in the female prison system.